Godhanger - King-Smith, Dick.; Davidson, Andrew (New York : Crown Publishers, 1999)
When a mysterious bird arrives in Godhanger Wood to protect the frightened animals from the cruel gamekeeper, this Christ-figure deliberately sacrifices himself to save them from death.
Keywords: Christian life -- Fiction; Allegories